International Libraries An Open Textbook - Reed, Amanda B.; Johnson, Sarah M.H; Severson, Heather; Green, Michael; Rubin, Melissa L.; Windholz, Anne; Dehais, Celia J.; Taylor, Hannah; Gilligan, Sioban; Wong, Mien; Cernik, Laura E.; Davis, Matthew C.; et al. (Open textbook library., 2023)
International Libraries: An Open Textbook is a reference sourcebook about the libraries and the field of librarianship in non-North American countries around the world. Each chapter in this volume includes a profile of a featured country’s variety of libraries, its library histories, its systems of library education, and its library practices, laws, and professional associations. Graduate students in the University at Buffalo’s Department of Information Science authored these chapters for the LIS 503: International Librarianship course during the summer term of 2019. The text was developed under the a Creative Commons license (CC BY-NC-SA 4.0) as an open educational resource that can be adapted for future sections of the International Librarianship course or for similar courses offered in library and information programs at other institutions.